TECHNOLOGY OF DYING OF POLYACRYLONITRILE AND MIXED COTTON-BASED FABRICS - N.M., Sharipova; Djumabeva, N.M. (Journal of Geography, Regional Planning and Development, 2024)
The purpose of this work is to study the process of dyeing knitted fabrics based on a mixture of cotton-nitron fibers with active and cationic dyes and to develop dyeing technology.